Liberalization and its consequences : a comparative perspective on Latin America and Eastern Europe - Love, Joseph LeRoy; Baer, Werner (Cheltenham, UK ; Northampton, MA, USA : E. Elgar, 2000)
The essays in this collection describe, analyze and compare the achievements and the failures of societies that adopted market-based economies within a democratic polity after a long period of communist rule or military authoritarianism.
Includes bibliographical references and index.
oif 21/09/15
Loan
Keywords: Privatization; Economic conditions; Economic policy; Democratization; Europe, Eastern; Latin America; Latin America; Europe, Eastern